Combinatorial Game Theory A Special Collection in Honor of Elwyn Berlekamp, John H. Conway and Richard K. Guy - Bonato, Anthony; Burke, Kyle; Carvalho, Alda; Clow, Alexander; Demaine, Erik D.; Diomidov, Yevhenii; Duchêne, Eric; Dufour, Matthieu; Dwyer, Aaron; Ferland, Matthew; Finbow, Stephen; Fisher, Michael; et al. (De Gruyter Proceedings in Mathematics, 2022)
Elwyn Berlekamp, John Conway, and Richard Guy wrote 'Winning Ways for your Mathematical Plays' and turned a recreational mathematics topic into a full mathematical fi eld. They combined set theory, combinatorics, codes, algorithms, and a smattering of other fi elds, leavened with a liberal dose of humor and wit. Their legacy is a lively fi eld of study that still produces many surprises. Despite being experts in other areas of mathematics, in the 50 years since its publication, they also mentored, talked, and played games, giving their time, expertise, and guidance to several generations of mathematicians. This volume is dedicated to Elwyn Berlekamp, John Conway, and Richard Guy. It includes 20 contributions from colleagues that refl ect on their work in combinatorial game theory